Supply Chain Management PT. MFM Ambon In Leihitu Barat District, Central Maluku District - Mitha Bazergan; Natelda R Timisela; Weldemina B Parera (Universitas Pattimura, 2023)
The research objective is to analyze the flow of raw materials, product flows, information flows, and cash flows in the supply chain at PT. MFM Central Maluku Regency. This study was analyzed using a descriptive method to describe the supply chain mechanism. The results showed that the nutmeg wine supply chain actors consisted of suppliers, producers, distributors, and consumers. Companies selling their products directly to consumers or through intermediaries occur through two supply chains. In the first supply flow, producers directly sell products to end consumers. Producers sell their products to intermediary traders and final consumers in the second supply chain. The flow of products from suppliers to intermediaries and then to consumers. Information flows flow in two directions, and financial flows flow in one direction from consumers to suppliers or from consumers to intermediaries and then suppliers.